Dnipropetrovsk histological school. Modern histology in the system of medical education, science and practice - Tverdokhleb, I. V. (Морфологія / Morphologia / Morfologìâ, 2015)
The presentation of the histological school of the Dnіpropetrovsk Medical Academy is a difficult and important task. It is difficult because Professor Vladimir Porfirievich Karpov is not only the founder of our histological department, but also the first rector of the Ekaterinoslav (Dnіpropetrovsk) Medical Academy.